Preparing the Intestine for Fibrocolonoscopy, What Should We Know? - Saidovich, Kadirov Bekhruzbek (Journal of Science in Medicine and Life, 2024)
The article, from the perspective of evidence-based medicine, examines the role of adequate bowel preparation in increasing the effectiveness of fibrocolonoscopy, formulates modern requirements for drugs to prepare for this procedure, and demonstrates the advantages of second-generation sulfate-free drugs based on macrogol. The main ways to improve compliance and increase the efficiency of bowel preparation, including the use of two-stage regimens, are considered; a reduction in the volume of solution for intestinal lavage and the use of combined regimens are justified.